CURRENT TRENDS IN THE FUNCTIONING OF THE REGIONAL LABOR MARKET - Kramareva, Olga; Nadtochii, Alla (Pressing Problems of Public Administration, 2021)
In the article was made the analysis of activity in the main spheres of production: industry, agriculture, construction and capital investments. This analysis was made by regions and for the whole country of Ukraine for the period of January - June 2020. The main trends (which are negative) have been identified. Together with the rapid reduction of the production volumes, industrial production decreased in 22 regions of Ukraine, agriculture degreased in 21 regions, construction sector decreased in 19 regions. Capital investments that allow for modernization and expansion of production in the country has almost halved. Reduction took place in 24 regions . The reason for this crisis in the basic sectors of the economy - stopping or restricting the operation of enterprises because of spread of coronavirus COVID-19. Small and medium-sized businesses focused on providing services in the field of tourism, beauty, catering, repair, transport were affected the most. Negative macroeconomic trends affected the labor market.In the article were revealed modern tendencies of functioning of the regional labor market. Analysis was done with accordance to three main indicators: demand, labor supply and salaries for the period from January to August 2020. We can see the negative tendency: reduce labor demand and mass layoffs of the employees in all regions of the country. In the article was analyzed planned and real state of unemployment. The real state appeared much worse. Another negative trend in demand is increase in hidden unemployment. It is appeared in sending employees on unpaid leave (mostly in Kyiv, Kyiv and Cherkasy regions) and transfer to part-time work, reduced working days or weeks (mostly in Dnipropetrovsk, Kharkiv regions and the city of Kyiv). This reduces the level of income and increases poverty among workers.The article showed a trend of significant growth in labor supply. It has increased not only due to laid off workers, but also for account of migrant workers who returned to Ukraine (due to reduced business activities in other countries). These workers used to get bigger (comparing to Ukrainian) salary, so often can not find jobs with proper salary. They often stop searching and do not always register with the employment services. Thus, the actual number of unemployed is much higher than the official one. In addition, migrant workers stopped transfer money to their families but need financial help for themselves. Labor supply was also increased by youth, which was focused on labor migration abroad. But due to the spread of the pandemic, the reduction of jobs there and migrant labor restrictions, youth stayed in Ukraine. Disparity between labor supply and demand is increasing in all regions of the country.The main trends in wage changes are identified. The average salary in Ukraine and in each of its regions has a tendency to grow. However, twice for the analyzed period it decreased. First time in April (during lockdown) then gradually increased until July, and in August decreased again. The Real salaries level in all regions have decreased. Especially it decreased in Luhansk, Cherkasy, Poltava and Rivne regions. To eliminate negative trends in the regional labor market business entities require government support. It can be done by preferential business loans, financial support for the self-employed, providing grants for startups, etc.